Acoustic Source Localization via Subspace Based Method Using Small Aperture MEMS Arrays. (15th July 2014) - Zhang, Xin; Song, Enliang; Huang, JingChang; Liu, Huawei; Wang, YuePeng; Li, Baoqing; Yuan, Xiaobing
Abstract : Small aperture microphone arrays provide many advantages for portable devices and hearing aid equipment. In this paper, a subspace based localization method is proposed for acoustic source using small aperture arrays. The effects of array aperture on localization are analyzed by using array response (array manifold). Besides array aperture, the frequency of acoustic source and the variance of signal power are simulated to demonstrate how to optimize localization performance, which is carried out by introducing frequency error with the proposed method. The proposed method for 5 mm array aperture is validated by simulations and experiments with MEMS microphone arrays. Different types of acoustic sources can be localized with the highest precision of 6 degrees even in the presence of wind noise and other noises. Furthermore, the proposed method reduces the computational complexity compared with other methods.